Relationship between soil phosphorus dynamics and low-phosphorus responses at specific root locations of white lupine. Issue 5 (2nd November 2022) - Kan, Ayane; Maruyama, Hayato; Aoyama, Nao; Wasaki, Jun; Tateishi, Yoshiko; Watanabe, Toshihiro; Shinano, Takuro
ABSTRACT: Phosphorus (P) is an essential element for crop production; however, availability tends to be low due to slow diffusion and high fixation in soils. To cope with phosphate deficiency, white lupines ( Lupinus albus L.) form unique root structures called cluster roots. The objective of this study was to elucidate detailed spatial differences of the mechanisms under low-P condition in the root system using rhizoboxes. We cultivated plants in rhizoboxes with P-deficient soil for 33 days. We then harvested roots and the adjacent soil from 128 compartments by dividing 2 × 2 cm squares in the rhizoboxes. We investigated relative expression levels of several genes that encode proteins assumed to be involved in P solubilization or translocation. Additionally, we analyzed fractionated P, soluble metal cations (Fe, Al, and Mn), and enzyme activities in the soil of each compartment. We observed a significant positive correlation between one of the MATE (multidrug and toxic compound extrusion/detoxification) genes, LaMATE6, and soluble metal cations, suggesting the secretion of citric acid into the rhizosphere via MATE proteins increased soluble metal cation concentrations. Furthermore, we demonstrated that roots in the same developmental stages were likely to have different influences on the mobilization of fractionated P in the rhizosphere soil. Our findings highlight the importance of investigating the relationship between soil chemical properties and root functions at a high spatial resolution to elucidate the detailed mechanisms of P mobilization by plants.